Polarization-independent electrically tunable/switchable airy beam based on polymer-stabilized blue phase liquid crystal - Luo, D. (2014)
Because of their non-diffraction and freely acceleration during propagation, finite energy Airy beams are interesting for application such as optical manipulation, plasma channel generation and optical vortex generation. Especially interesting are tunable/switchable Airy beams, in which the Airy beam tuning by electric field, temperature or optical intensity can be realized. Here we experimentally demonstrate polarization-independent, electrically tunable/switchable Airy beam based on polymer-stabilized blue phase liquid crystals with wide working temperature range and fast response time through a structure called vertical field driven mode.